PERBEDAAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA BALITA DENGAN DIARE DI DESA DAN DI KOTA - Ratih Ayuningtiyas; Tika Yolanda (Collaborative Medical Journal, 2022)
Diarrhea is a disease characterized by changes in the consistency of the stool apart from the frequency of bowel movements. Diarrhea is the second leading cause of death for children under five in the world. Diarrhea is still a public health problem in developing countries, including Indonesia. Based on data from the Ministry of Health of the Republic of Indonesia 2017, in 2016 Riau Province was in the 10th position out of all provinces in Indonesia with 171,299 diarrhea cases. One of the efforts to prevent and overcome diarrhea can be done by counseling the community to improve Clean and Healthy Life Behavior (CHLB) in daily life. According to the results of Riskesdas 2013, there are differences in the proportion of households with CHLB in both urban and rural areas. The purpose of this study was to determine the difference between CHLB in children under five with diarrhea in the village and in the city. The type of research is analytic observational research, with a cross sectional research design. The sampling technique was quota sampling and statistically tested using the Mann Whitney test. From the results of the research, a p value of 0.065 (p value > 0.05) shows that there is no difference in CHLB in toddlers with diarrhea in rural and urban areas and it can be concluded that there is no significant difference between lifestyle behaviors clean and healthy for toddlers with diarrhea in rural and urban areas.